Virginia at war, 1861 - Davis, William C., 1946-; Robertson, James I., Jr. (James Irvin), 1930-2019 (Virginia at war series., 2005)
More Civil War battles were fought on Virginian soil than on that of any other Confederate state. No state suffered more from invasion and occupation than the Old Dominion, and none witnessed as much of the war. Virginia's story of the Civil War stands unique among the Confederate States. Virginia at War, 1861 looks at Virginia on the eve of secession, detailing the activities of the convention that finally took the state out of the Union and explaining how Richmond became the capital of the new Confederate nation. Chapters in the book examine Virginia's private state army and its little-known.